Thirteen ribs and long gap oesophageal atresia: The embryological hypothesis for exploration - Ramesh B Hatti; Anita H Nyamagoudar; Timman Gouda R. Patil; Sunil J Patil; Rajendra T Patil; Praveen R Pylla (Wolters Kluwer Medknow Publications, 2020)
Context: Since the gap between two atretic segments of oesophagus is a critical determinant of prognosis for oesophageal atresia/tracheoesophageal fistula (EA/TEF), the search for a surrogate non-invasive pre-operative marker of long gap atresia continues. Aims: The purpose of the study was to compare the presence of normal and supernumerary ribs with length of EA and survival rates. Settings and Design: A prospective observational study was conducted at a tertiary care referral neonatal intensive care unit in North Karnataka, India, from January 2016 to June 2019. Subjects and Methods: Amongst babies with EA/TEF, pre-operative radiograph helped determine the number of ribs, and babies were divided into two groups; Group I: babies with 12 ribs and Group II: babies with supernumerary ribs. Statistical Analysis Used: Nominal variables were expressed as percentage and continuous variables as mean standard deviation. MedCalc software was used to compare proportions and means. A P < 0.05 was considered statistically significant. Results: Of the 61 cases, 51 were operated. Long gap EA was predominantly seen amongst babies in Group II (40% in Group II vs. 27% in Group I, P= 0.424). Survival rates by percentage were lower in babies in Group II (60% in Group II vs. 80% in Group I, P= 0.188). Both the above findings were proven statistically insignificant. The overall survival rate amongst the study population was 78.4% (39/51). Conclusions: Supernumerary ribs were associated with a higher occurrence of long gap EA and lower survival rates, though statistically insignificant. Multicentre collaboration may provide significant input for strengthening or refuting the above hypothesis.